(untitled) (Journal of Engineering Science, 2020)
Corrosion of reinforcement is an important durability concern for the structures exposed to coastal regions. Since corrosion of reinforcement involves long periods of time, impressed current technique is usually used to accelerate the corrosion of reinforcement in laboratories. Characterization of impressed current technique was the main focus of this research,which involved determination of optimum chloride content and minimum immersion time of specimens for which the application of Faraday’s law could be efficient. To obtain optimum chloride content, the electrolytes in the corrosion cell were prepared similar to that of concrete pore solutions. Concrete prisms of 200 mm by 200 mm by 300 mm were used to determine the minimum immersion time for saturation. It was found that the optimum chloride content was 35 gm/L and the minimum immersion time for saturation was 140 hours. Accounting the results, a modified expression based on Faraday’s law was proposed to calculate weight loss due to corrosion. Journal of Engineering Science 11(1), 2020, 93-99